Effective Treatment Time Using a Magnetic Field to Increase Soybean (Glycine max) Productivity - Mokhamad Tirono; Farid Samsu Hananto (Postgraduate, University of Mataram, 2023)
Increasing the productivity of soybean plants using environmentally friendly techniques is urgently needed. This study aimed to determine the magnetic field (MF) treatment time that can optimize soybean growth and productivity. This study used soybean seed samples of the Grobogan variety. The seeds were obtained from the Research Institute for Various Nuts and Roots-Indonesia. The treatment was performed using MF of 0.3 mT, with treatment times varying from 0 to 30 minutes. Each treatment group was repeated once a day for five days. This study obtained the results that the time of MF treatment affected the sprouts' emergence time, plant growth, fruiting time, seed weight, and production per plant. Optimal results were obtained from seeds treated with a MF for 20 minutes. Treatment with time-varying MF requires lower magnetic flux density (MFD) and treatment time than stationary MF. Treatment time that is too long can reduce germination, plant growth, and soybean productivity